The pH-triggered polyglutamate brush co-delivery of MDR1 and survivin-targeting siRNAs efficiently overcomes multi-drug resistance of NSCLC. (1st November 2020) - Wang, Zhongjuan; Liang, Yueqin; Liu, Yanqiu; Xia, Hongying; Liu, Jianqi; Jin, Xingfang; Li, Zhongkun
Abstract: Multi-drug resistance (MDR) is one of the major challenges in the successful chemotherapy of non-small cell lung cancer (NSCLC). Although RNA interference (RNAi) has been widely used to silence resistance-related genes, the effect remains unsatisfactory. In this study, we attempted to overcome MDR of NSCLC by simultaneously interfering with two RNAs that have different functions. A new pH-triggered polyglutamate brush polymer dimethylmaleic anhydride-poly(ethyleneglycol) monomethyl ether-b-polyglutamate-g-spermine (DMA-mPEG-b-PG-g-spermine, DPPGS) was designed and synthesized. The DPPGS/small interfering RNA (siRNA) complex nanoparticles (DPPGSN) were prepared. The results demonstrated that DPPGSN could be transformed from a negatively charged form into a positively charged form in the slightly acidic tumor extracellular environment. The siRNA targeting MDR1 mRNA (siMDR1) and siRNA targeting survivin mRNA (siSurvivin) could be efficiently co-delivered by DPPGS to simultaneously interfere with two genes ( p < 0.01). Furthermore, DPPGS co-delivery of siMDR1 and siSurvivin lowered the IC50 value of cisplatin (DDP) in A549/DDP ( p < 0.01) cells and increased the apoptosis rate of the cells ( p < 0.01). Therefore, co-delivery of siMDR1 and siSurvivin using DPPGS would be a promising approach for overcoming MDR of NSCLC.